UJI AKTIVITAS ANTIOKSIDAN DAN TABIR SURYA EKSTRAK ETANOL DAN FRAKSI DAUN TERAP (Artocarpus odoratissimus Blanco) - Furi, Mustika; Feriansyah, Robby; Fadhli, Haiyul; Utami, Rahayu; Lestari, Putri (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Plants from genus Artocarpus are known containing phenolic and flavonoid compounds that have potential as antioxidant and sunscreen agent. Terap is one of species plant of Artocarpus genus, which has latin name Artocarpus odorratissimus Blanco. This present study aims to determine the antioxidant and sunscreen activity of ethanol extract and fractions of terap’s leaves. The evaluation was conducted by in vitro assay, which were the antioxidant activity was tested using the DPPH method by Microplate Reader and the sunscreen activity was analyzed using UV-Vis spectrophotometer. The results indicated that ethanol extract, ethylacetate and butanol fractions afforded very strong category of antioxidant activity with IC50 values ​​of 44.04; 42.9 and 36.49 µg/mL, respectively, while moderate activity gave by n-hexane fraction with IC50 value of 168.31 µg/mL. As for the sunscreen activity test, the most potential activity exhibited by the ethylacetate fraction at tested concentrations of 500; 250; 200; and 150 µg/mL demonstrated SPF values of 39.45; 37.36; 33.27 and 26.14, respectively; with ultra protection category as well as showed %Te and %Tp values of <1% which categorized as sunblock.